A multiaxis device for in‐focus manipulation of objects under a dissecting microscope. (4th July 2014) - GRAS, HERIBERT
Summary An inexpensive specimen holder for objects under a dissecting microscope is described which allows arbitrary orientation and rotation of the object within the visual field and focal plane of the microscope. Based on a spherical cap upon a magnet, this apparatus is easy to construct and permits single‐handed manipulation of the specimen from some distance. Precise positioning is demonstrated for halteres of Drosophila under up to 120× magnification. Because of the restricted field of view and depth of focus of a dissecting microscope, it is often difficult to position tiny objects under study in varying orientation, especially if the specimen must simultaneously be dissected with forceps, microscissors or needles. The problem is solved most conveniently with a specimen holder based on a spherical cap which is held by a strong magnet on a steel ring. The specimen tilts vertically in any direction by up to 70° and—even in oblique orientation—rotates through 360° around the sphere's centre in the focal plane. By help of an interleaved plastic foil in a ring carrier, these movements can be controlled unimanually from outside the visual field.